High-strength flow-state solidified soil and preparation method thereof

By using specific raw materials and preparation methods in the fluid-standed soil, high-strength fluid-standed soil is formed, which solves the problems of poor compressive strength, crack strength and frost resistance in the prior art, and achieves high-performance applications in extreme environments.

CN119797843APending Publication Date: 2025-04-11JIANGSU SANHEJIAN ENVIRONMENTAL PROTECTION TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510009232.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When used in extreme environments, existing fluid solidified soil has poor compressive strength, cracking strength, frost resistance, and insufficient durability, which limits its application in environments such as large changes in temperature and humidity and freeze-thaw cycles.

Method used

The preparation method of high-strength fluid-standed soil is adopted, including the use of raw materials such as inorganic construction waste aggregate, engineering waste soil, cement, tailings slag, composite curing agent, carbon materials, sisal fibers and basalt fibers, and through specific stirring and maintenance processes, a fluid-standed soil with high strength and durability is formed.

Benefits of technology

It significantly enhances the internal structure of the soil, improves compressive strength, crack strength and frost resistance, and extends its service life, making it suitable for buildings, bridges, tunnels and underground projects in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005227860070000161
    Figure BDA0005227860070000161
  • Figure BDA0005227860070000171
    Figure BDA0005227860070000171
  • Figure BDA0005227860070000172
    Figure BDA0005227860070000172
Patent Text Reader

Abstract

The invention discloses high-strength flow-state solidified soil and a preparation method thereof, and relates to the field of building materials. Preparing core-shell modified polypropylamide and a composite curing agent, and pretreating the inorganic construction waste, the engineering spoil and the carbon material; adding the inorganic construction waste aggregate, the tailing slag, the sisal fibers and the basalt fibers into a stirrer, and stirring; adding the engineering spoil, the cement and the carbon material into the stirrer and stirring; pouring the water reducing agent solution into the stirrer in batches, and stirring; adding a composite curing agent into the stirrer, and stirring to obtain high-strength flow-state solidified soil slurry; and filling the obtained high-strength flow-state solidified soil slurry into a backfilling groove, vibrating, and maintaining under a constant temperature and humidity condition. The concrete has the advantages of fluidity, uniformity, low permeability, self-compaction and self-maintenance capability, high and low temperature resistance, freezing and thawing resistance, high crack resistance and compressive strength, can obviously enhance the internal structure of a soil body, and can be applied to the fields of buildings, bridges, tunnels and underground engineering in extreme environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a high-strength fluidized solidified soil and a preparation method thereof. Background Art

[0002] Fluidized solidified soil is prepared by adding curing agent, necessary water and additives to pretreated sand or mud, and mixing them evenly with a specific mixer. The prepared mixture has a certain fluidity and can be used for pouring construction. After filling and curing, it solidifies into a geotechnical engineering material with a certain strength, water stability and low permeability.

[0003] Construction waste refers to waste generated during construction, demolition, renovation and other related projects. These wastes usually include materials such as concrete, bricks, wood, metal, glass, plastic, gypsum board, etc. The generation of construction waste is an inevitable part of the construction industry, but its treatment and management is an important environmental and social issue.

[0004] There are still many defects in the existing technology of fluidized solidified soil, including low compressive strength, low crack resistance, poor frost resistance, poor environmental adaptability, insufficient durability, etc., which greatly limit the application of fluidized solidified soil in extreme environments such as large changes in temperature and humidity and freeze-thaw cycles. The industry needs a fluidized solidified soil that can significantly enhance the internal structure of the soil and can be used in buildings, bridges, tunnels and underground engineering fields in extreme environments. Summary of the invention

[0005] The object of the present invention is to provide a high-strength fluidized solidified soil and a preparation method thereof to solve the problems raised in the background technology.

[0006] In the first aspect, the present invention provides a high-strength fluidized solidified soil, which adopts the following technical solution:

[0007] A high-strength fluidized solidified soil, comprising the following raw materials in parts by weight:

[0008] 550-594 parts of inorganic construction waste aggregate;

[0009] 204-254 pieces of engineering waste soil;

[0010] Cement 75-84 parts;

[0011] Tailings 54-58 parts;

[0012] Composite curing agent 98-114 parts;

[0013] 3.8-11.2 parts of carbon material;

[0014] Sisal fiber 2.9-5.8 parts;

[0015] Basalt fiber 2.9-3.1 parts;

[0016] Polycarboxylate water reducer 4-5.6 parts;

[0017] 85-98.5 parts of distilled water;

[0018] Furthermore, the inorganic construction waste aggregate is obtained by pre-processing of waste construction concrete and waste bricks and stones through crushing and screening;

[0019] Furthermore, the engineering waste soil is obtained by drying and screening the slag and sludge in the pre-treatment steps;

[0020] Furthermore, the tailings are copper ore tailings;

[0021] It should be noted that the main components of copper mine tailings are silicon dioxide, ferric oxide and aluminum oxide.

[0022] Furthermore, the specific preparation steps of the composite curing agent are as follows:

[0023] The core-shell modified polyacrylamide was dispersed in deionized water at room temperature and homogenized for 15-20 minutes, a cross-linking agent was added, and the mixture was stirred for 5-8 minutes. Sodium bicarbonate was added and stirred until it was completely dissolved. Waste brick powder was added and stirred until the waste brick powder was evenly dispersed in the system. Water glass was added and stirred until the waste brick powder particles had no longer precipitation. The mixture was allowed to stand for 12 hours to obtain a composite curing agent.

[0024] Furthermore, the specific preparation steps of the core-shell modified polyacrylamide are as follows:

[0025] Graphene oxide was ultrasonically dispersed in deionized water, acrylamide was added, and the mixture was stirred at 800 r / min at room temperature for 30 min. Polyethylene glycol was added and stirred at 800 r / min at 60 °C until the polyethylene glycol was completely dissolved. N,N-methylenebisacrylamide and tetramethylethylenediamine were added and stirred at 600 r / min for 20 min. Ammonium persulfate APS was added and homogenized for 3 min. The mixture was allowed to stand at 60 °C for 3 h to obtain core-shell modified polyacrylamide.

[0026] It should be noted that polyethylene glycol and graphene oxide are encapsulated in polyacrylamide by free radical polymerization to obtain core-shell modified polyacrylamide, namely PAM@rGo / PEG core-shell material. Graphene oxide has a unique layered structure and intrinsic band gap, and can be used to prepare solid-solid phase change materials based on polyethylene glycol. At the same time, graphene oxide has a large specific surface area and open pores, which can provide excellent adsorption and support for the embedding of polyethylene glycol. Polyacrylamide has excellent chemical stability and good thermal conductivity, and can be used as an ideal support material for encapsulating phase change materials, which can solve the leakage problem of polyethylene glycol and further improve the cyclic stability of phase change materials. The combination of graphene oxide, polyethylene glycol and polyacrylamide does not produce new substances, and polyethylene glycol and polyacrylamide gel have good biocompatibility.

[0027] It needs to be explained again that, on the one hand, core-shell modified polyacrylamide is a component of the composite curing agent. The hydroxyl and carboxyl groups on the surface and between the layers of layered graphene oxide can interact with the amide groups of the polyacrylamide molecular chain. Graphite powder, as a rigid structure, can support the flexible skeleton of the original polyacrylamide molecular chain, synergistically enhance the viscoelasticity, thermal stability, tensile properties and plugging ability of the core-shell modified polyacrylamide, and improve the elastic modulus, phase transition temperature and tensile stress of the core-shell modified polyacrylamide gel. When it is added to the fluidized solidified soil, it can effectively reduce the permeability of the fluidized solidified soil, and improve the plugging effect when cracks occur. On the other hand, core-shell modified polyacrylamide as a phase change material added to the fluidized solidified soil can improve the thermal energy regulation capacity of the fluidized solidified soil, improve its resistance to high and low temperatures, reduce the energy consumption of buildings caused by temperature changes, and extend its service life.

[0028] Furthermore, the inorganic construction waste aggregate has a particle size of 5-15 mm.

[0029] Furthermore, the particle size of the engineering waste soil is 0.15-5 mm, and the water absorption rate is 14.7%-20%.

[0030] Furthermore, the mass ratio of the core-shell modified polyacrylamide, deionized water, crosslinking agent, sodium bicarbonate, waste brick powder and water glass is 0.2:(25-43):(0.4-2.0):2:(10-13):17.

[0031] It should be noted that the main curing components of the composite curing agent are waste brick powder, water glass and core-shell modified polyacrylamide. The main components of waste brick powder are silicon dioxide and aluminum oxide. When added to the composite curing agent, it will hinder the hydration process and reduce the formation of hydration products, thereby reducing the self-shrinkage of the composite curing agent mixed cementitious material; water glass can be used as an inorganic curing agent. It reacts with aluminum, iron and other ions in the soil to form silicate gel, which can not only improve the density of the fluidized solidified soil, but also improve its heat resistance; core-shell modified polyacrylamide can improve the water retention rate and frost resistance of the soil and extend its service life.

[0032] Furthermore, the cross-linking agent is one of aluminum citrate, aluminum chloride and aluminum sulfate; the particle size of the waste brick powder is 0.05-0.15 mm; and the modulus of water glass is 2.2-2.6.

[0033] Furthermore, the usage ratio of the graphene oxide, deionized water, acrylamide, polyethylene glycol, N,N-methylenebisacrylamide, tetramethylethylenediamine and ammonium persulfate is 0.2g:12mL:2g:(12.09-13)g:0.02g:20μL:0.02g; the molecular weight of polyethylene glycol is 3000-10000.

[0034] Furthermore, the carbon material is pretreated biochar, and the pretreatment method is as follows:

[0035] Soak the biochar in water at 25°C for 24 hours, take it out and place it on a strainer until there is no continuous dripping, spread it flat and place it in a drying oven at 120°C to dry for 10-15 minutes.

[0036] It should be noted that biochar has a large number of pore structures inside, including open pores and closed pores, which makes it highly absorbent and can give the fluidized solidified soil a self-curing effect: biochar with high water demand has the ability to absorb free water in the fluidized solidified soil, and the water absorbed in the biochar is released over time, saturating the capillary porosity of the soil, ultimately helping to minimize the self-shrinkage phenomenon in the fluidized solidified soil, reducing the risk of cracking caused by uneven deformation of concrete, thereby improving the compressive strength.

[0037] It needs to be explained again that when pre-treated carbon materials are added to the fluidized solidified soil, more water will be attached to the surface of the biochar, which will cause excess water to enter the concrete raw materials, increase its water-cement ratio, and reduce the strength of the soil after curing; the water carried inside the biochar will decrease, affecting the effective water-cement ratio, making the workability of the concrete worse, and affecting the internal self-curing during the curing process. Therefore, it is necessary to pre-treat the bamboo biochar so that the pores of the biochar are filled with water and the surface is free of water.

[0038] Furthermore, the sisal fiber is sisal fiber with a length of 3-4 cm and a breaking elongation of 4%-6%.

[0039] It should be noted that the addition of sisal fiber can prevent the fluidized solidified soil from cracking or cracks from developing downward. On the one hand, the friction between the fluidized solidified soil particles and the sisal fiber partially offsets the tensile stress when pulled horizontally, thereby reducing the opening of the cracks; on the other hand, the sisal fiber can combine with the shell material polyacrylamide of the core-shell modified polyacrylamide in the composite curing agent and the soil particles to form agglomerates, which can reduce the evaporation rate, keep the fluidized solidified soil moist for a long time, and delay the occurrence of cracks. It is worth mentioning that when sisal fiber or core-shell modified polyacrylamide is added to the fluidized solidified soil alone, the crack resistance and water retention properties of the fluidized solidified soil cannot be improved at the same time.

[0040] Furthermore, the basalt fiber has a density of 2.5-2.8 g / cm3 and a tensile strength of 3.5-4 GPa.

[0041] It should be noted that when fluidized solidified soil is used in dry-wet states and in environments with large changes in temperature and humidity, dry-wet cycles will lead to extensive water migration, changes in particle arrangement, the generation of microcracks, a decrease in density and an increase in porosity. When water is absorbed and evaporated inside the soil, aggregates and particles tend to shrink and crack, the heterogeneity of the soil increases, and the cohesion between particles is significantly reduced. During the freeze-thaw cycle, due to the continuous solid-liquid transition of pore water in the soil, the pore volume inside the soil increases, the pores between aggregates gradually increase, and the strength decreases. In addition, freeze-thaw cycles lead to changes in particle displacement and pore morphology, and the evolution of pores and reduced connectivity lead to the generation of microcracks, which not only accelerates the increase in particle spacing, but also aggravates the destruction of particle aggregates. Sisal fibers, composite curing agents and soil particles combine to form aggregates, filling most of the pore space; basalt fibers play the role of bridging, anchoring and wrapping aggregates, increasing the contact area between fibers and soil particles, and helping to form a more stable internal structure.

[0042] It needs to be reiterated that the use of composite materials to solidify soil has gradually become a current development trend. Sustainable and green solidification materials are constantly being discovered, and the interaction between various materials can make up for the shortcomings of the soil and enhance the advantages. The synergistic effect between various materials in the present invention significantly enhances the internal structure of the soil and reduces the deformation characteristics, thereby showing higher shear strength and more stable other properties.

[0043] In a second aspect, the present invention further provides a method for preparing the above-mentioned high-strength fluidized solidified soil, comprising the following steps:

[0044] S1. Add inorganic construction waste aggregate, tailings, sisal fiber and basalt fiber into the mixer according to the proportion and stir for 5-8 minutes;

[0045] S2. Add engineering waste soil, cement and carbon materials into the mixer according to the proportion and stir for 5-8 minutes;

[0046] S3, dissolving the polycarboxylate water reducer in distilled water and homogenizing to obtain a water reducer solution, pouring half of the water reducer solution into a mixer and stirring for 3-5 minutes, adding the remaining water reducer solution and continuing to stir until the slurry is completely fluidized in the mixer;

[0047] S4. Add the composite curing agent into the mixer according to the proportion, stir for 3-5 minutes, and obtain a high-strength fluidized solidified soil slurry;

[0048] S5. The high-strength fluidized solidified soil slurry obtained in S4 is loaded into the backfill tank and vibrated, and then cured for 24-48 hours under constant temperature and humidity conditions.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] 1. Adding core-shell modified polyacrylamide to fluidized solidified soil can effectively reduce the permeability of fluidized solidified soil, and improve the blocking effect when cracks occur; at the same time, it can be used as a phase change material to improve the thermal energy regulation ability of fluidized solidified soil, improve its high and low temperature resistance, reduce the energy consumption of buildings caused by temperature changes, improve the water retention rate and frost resistance of the soil, and extend its service life; the addition of composite curing agent to fluidized solidified soil can not only improve the density of fluidized solidified soil, but also improve its heat resistance.

[0051] 2. Adding carbon materials whose pores are filled with water and whose surface is free of moisture to the fluidized solidified soil can help minimize the self-shrinkage inside the fluidized solidified soil and reduce the risk of cracking caused by uneven deformation of concrete, thereby improving the compressive strength.

[0052] 3. The addition of sisal fiber can prevent the fluidized solidified soil from cracking or cracking downward, offset and reduce the opening of cracks. At the same time, sisal fiber can combine with the composite curing agent and soil particles to form agglomerates, which can reduce the evaporation rate, keep the fluidized solidified soil moist for a long time, and delay the generation of cracks. When the fluidized solidified soil is used in a dry-wet state and in an environment with large changes in temperature and humidity and freeze-thaw cycles, basalt fiber can bridge, anchor and wrap the agglomerates to form a more stable internal structure, reduce deformation characteristics, and show higher shear strength.

[0053] 4. The high-type fluidized solidified soil prepared by the present invention has fluidity, uniformity and low permeability, has self-compacting and self-maintaining capabilities, has reduced self-shrinkage, is resistant to high and low temperatures, resistant to freezing and thawing, has high crack resistance and compressive strength, and significantly enhances the internal structure of the soil. It can be used in buildings, bridges, tunnels and underground engineering fields under extreme environments. DETAILED DESCRIPTION

[0054] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] The preparation steps of the composite curing agent are as follows:

[0056] At room temperature, 0.2 g of core-shell modified polyacrylamide was dispersed in 34 g of deionized water and homogenized for 15-20 min, 1.2 g of aluminum citrate crosslinker was added, stirred for 5-8 min, 2 g of sodium bicarbonate was added, stirred until completely dissolved, 11.5 g of waste brick powder with a particle size of 0.05-0.15 mm was added, stirred until the waste brick powder was evenly dispersed in the system, 17 g of water glass with a modulus of 2.2-2.6 was added, stirred until the waste brick powder particles had no longer precipitation, and allowed to stand for 12 h to obtain a composite solidification.

[0057] The core-shell modified polyacrylamide preparation steps are as follows:

[0058] 0.2 g of graphene oxide was ultrasonically dispersed in 12 mL of deionized water, 2 g of acrylamide was added, and the mixture was stirred at 800 r / min for 30 min at room temperature. 12.6 g of polyethylene glycol with a molecular weight of 6000 was added, and the mixture was stirred at 800 r / min at 60 ° C until the polyethylene glycol was completely dissolved. 0.02 g of N,N-methylenebisacrylamide and 20 μL of tetramethylethylenediamine were added, and the mixture was stirred at 600 r / min for 20 min. 0.02 g of ammonium persulfate APS was added, and the mixture was homogenized for 3 min. The mixture was allowed to stand at 60 ° C for 3 h to obtain core-shell modified polyacrylamide.

[0059] The carbon material pretreatment steps are as follows:

[0060] Soak the biochar in water at 25°C for 24 hours, take it out and place it on a strainer until there is no continuous dripping, spread it flat and place it in a drying oven at 120°C to dry for 15 minutes.

[0061] Example 1

[0062] A high-strength fluidized solidified soil, comprising the following raw materials in parts by weight:

[0063] 572 parts of inorganic construction waste aggregate (obtained by crushing and screening discarded building concrete and discarded bricks and stones, with a particle size of 5-15 mm);

[0064] 229 pieces of engineering waste soil (obtained through drying and sieving of slag and silt, with a particle size of 0.15-5mm and a water absorption rate of 14.7%-20%);

[0065] Cement 79.5 parts (P.O42.5);

[0066] 56 parts of copper mine tailings;

[0067] 106 parts of composite curing agent;

[0068] 7.5 parts of carbon material;

[0069] 4.4 parts of sisal fiber (length 3-4 cm, elongation at break 4%-6%);

[0070] 3 parts of basalt fiber (density 2.5-2.8g / cm3, tensile strength 3.5-4GPa);

[0071] 4.8 parts of polycarboxylate water reducer;

[0072] 91.8 parts of distilled water.

[0073] A method for preparing high-strength fluidized solidified soil, the method comprising the following steps:

[0074] S1. Add inorganic construction waste aggregate, tailings, sisal fiber and basalt fiber into the mixer according to the proportion and stir for 8 minutes;

[0075] S2. Add engineering waste soil, cement and carbon materials into the mixer according to the proportion and stir for 8 minutes;

[0076] S3, dissolving the polycarboxylate water reducer in distilled water and homogenizing to obtain a water reducer solution, pouring half of the water reducer solution into a mixer and stirring for 5 minutes, adding the remaining water reducer solution and continuing to stir until the slurry is completely fluidized in the mixer;

[0077] S4, adding composite curing agent into the mixer according to the proportion, stirring for 5 minutes, and obtaining high-strength fluidized solidified soil slurry;

[0078] S5. The high-strength fluidized solidified soil slurry obtained in S4 is loaded into the backfill tank and vibrated, and then cured for 24 hours under constant temperature and humidity conditions.

[0079] Example 2

[0080] A high-strength fluidized solidified soil, comprising the following raw materials in parts by weight:

[0081] 550 parts of inorganic construction waste aggregate (obtained by crushing and screening discarded building concrete and discarded bricks and stones, with a particle size of 5-15 mm);

[0082] 204 parts of engineering waste soil (obtained through drying and sieving of slag and silt, with a particle size of 0.15-5mm and a water absorption rate of 14.7%-20%);

[0083] Cement 75 parts (P.O42.5);

[0084] 54 parts of copper mine tailings;

[0085] Composite curing agent 98 parts;

[0086] 3.8 parts of carbon material;

[0087] 2.9 parts of sisal fiber (length 3-4 cm, elongation at break 4%-6%);

[0088] 2.9 parts of basalt fiber (density 2.5-2.8g / cm3, tensile strength 3.5-4GPa);

[0089] 4 parts of polycarboxylate water reducer;

[0090] 85 parts of distilled water.

[0091] A method for preparing high-strength fluidized solidified soil, the method comprising the following steps:

[0092] S1. Add inorganic construction waste aggregate, tailings, sisal fiber and basalt fiber into the mixer according to the proportion and stir for 8 minutes;

[0093] S2. Add engineering waste soil, cement and carbon materials into the mixer according to the proportion and stir for 8 minutes;

[0094] S3, dissolving the polycarboxylate water reducer in distilled water and homogenizing to obtain a water reducer solution, pouring half of the water reducer solution into a mixer and stirring for 5 minutes, adding the remaining water reducer solution and continuing to stir until the slurry is completely fluidized in the mixer;

[0095] S4, adding composite curing agent into the mixer according to the proportion, stirring for 5 minutes, and obtaining high-strength fluidized solidified soil slurry;

[0096] S5. The high-strength fluidized solidified soil slurry obtained in S4 is loaded into the backfill tank and vibrated, and then cured for 24 hours under constant temperature and humidity conditions.

[0097] Example 3

[0098] A high-strength fluidized solidified soil, comprising the following raw materials in parts by weight:

[0099] 594 parts of inorganic construction waste aggregate (obtained by crushing and screening discarded building concrete and discarded bricks and stones, with a particle size of 5-15 mm);

[0100] 254 pieces of engineering waste soil (obtained through drying and screening of slag and sludge, with a particle size of 0.15-5mm and a water absorption rate of 14.7%-20%);

[0101] Cement 84 parts (P.O42.5);

[0102] 58 parts of copper mine tailings;

[0103] Composite curing agent 114 parts;

[0104] 11.2 parts of carbon material;

[0105] 5.8 parts of sisal fiber (length 3-4 cm, elongation at break 4%-6%);

[0106] 3.1 parts of basalt fiber (density 2.5-2.8g / cm3, tensile strength 3.5-4GPa);

[0107] 5.6 parts of polycarboxylate water reducer;

[0108] 98.5 parts of distilled water.

[0109] A method for preparing high-strength fluidized solidified soil, the method comprising the following steps:

[0110] S1. Add inorganic construction waste aggregate, tailings, sisal fiber and basalt fiber into the mixer according to the proportion and stir for 8 minutes;

[0111] S2. Add engineering waste soil, cement and carbon materials into the mixer according to the proportion and stir for 8 minutes;

[0112] S3, dissolving the polycarboxylate water reducer in distilled water and homogenizing to obtain a water reducer solution, pouring half of the water reducer solution into a mixer and stirring for 5 minutes, adding the remaining water reducer solution and continuing to stir until the slurry is completely fluidized in the mixer;

[0113] S4, adding composite curing agent into the mixer according to the proportion, stirring for 5 minutes, and obtaining high-strength fluidized solidified soil slurry;

[0114] S5. The high-strength fluidized solidified soil slurry obtained in S4 is loaded into the backfill tank and vibrated, and then cured for 24 hours under constant temperature and humidity conditions.

[0115] Comparative Example 1

[0116] A high-strength fluidized solidified soil, comprising the following raw materials in parts by weight:

[0117] 572 parts of inorganic construction waste aggregate (obtained by crushing and screening discarded building concrete and discarded bricks and stones, with a particle size of 5-15 mm);

[0118] 229 pieces of engineering waste soil (obtained through drying and sieving of slag and silt, with a particle size of 0.15-5mm and a water absorption rate of 14.7%-20%);

[0119] Cement 79.5 parts (P.O42.5);

[0120] 56 parts of copper mine tailings;

[0121] 106 parts of water glass (modulus is 2.2-2.6);

[0122] 7.5 parts of carbon material;

[0123] 4.4 parts of sisal fiber (length 3-4 cm, elongation at break 4%-6%);

[0124] 3 parts of basalt fiber (density 2.5-2.8g / cm3, tensile strength 3.5-4GPa);

[0125] 4.8 parts of polycarboxylate water reducer;

[0126] 91.8 parts of distilled water.

[0127] A method for preparing high-strength fluidized solidified soil, the method comprising the following steps:

[0128] S1. Add inorganic construction waste aggregate, tailings, sisal fiber and basalt fiber into the mixer according to the proportion and stir for 8 minutes;

[0129] S2. Add engineering waste soil, cement and carbon materials into the mixer according to the proportion and stir for 8 minutes;

[0130] S3, dissolving the polycarboxylate water reducer in distilled water and homogenizing to obtain a water reducer solution, pouring half of the water reducer solution into a mixer and stirring for 5 minutes, adding the remaining water reducer solution and continuing to stir until the slurry is completely fluidized in the mixer;

[0131] S4. Add water glass into the mixer according to the proportion and stir for 5 minutes to obtain a high-strength fluidized solidified soil slurry;

[0132] S5. The high-strength fluidized solidified soil slurry obtained in S4 is loaded into the backfill tank and vibrated, and then cured for 24 hours under constant temperature and humidity conditions.

[0133] The difference between this comparative example and Example 1 is that no composite curing agent is used, but water glass is used as the curing agent.

[0134] Comparative Example 2

[0135] A high-strength fluidized solidified soil, comprising the following raw materials in parts by weight:

[0136] 572 parts of inorganic construction waste aggregate (obtained by crushing and screening discarded building concrete and discarded bricks and stones, with a particle size of 5-15 mm);

[0137] 229 pieces of engineering waste soil (obtained through drying and sieving of slag and silt, with a particle size of 0.15-5mm and a water absorption rate of 14.7%-20%);

[0138] Cement 79.5 parts (P.O42.5);

[0139] 56 parts of copper mine tailings;

[0140] 106 parts of composite curing agent;

[0141] 4.4 parts of sisal fiber (length 3-4 cm, elongation at break 4%-6%);

[0142] 3 parts of basalt fiber (density 2.5-2.8g / cm3, tensile strength 3.5-4GPa);

[0143] 4.8 parts of polycarboxylate water reducer;

[0144] 91.8 parts of distilled water.

[0145] A method for preparing high-strength fluidized solidified soil, the method comprising the following steps:

[0146] S1. Add inorganic construction waste aggregate, tailings, sisal fiber and basalt fiber into the mixer according to the proportion and stir for 8 minutes;

[0147] S2. Add engineering waste soil and cement into the mixer according to the proportion and stir for 8 minutes;

[0148] S3, dissolving the polycarboxylate water reducer in distilled water and homogenizing to obtain a water reducer solution, pouring half of the water reducer solution into a mixer and stirring for 5 minutes, adding the remaining water reducer solution and continuing to stir until the slurry is completely fluidized in the mixer;

[0149] S4, adding composite curing agent into the mixer according to the proportion, stirring for 5 minutes, and obtaining high-strength fluidized solidified soil slurry;

[0150] S5. The high-strength fluidized solidified soil slurry obtained in S4 is loaded into the backfill tank and vibrated, and then cured for 24 hours under constant temperature and humidity conditions.

[0151] The difference between this comparative example and Example 1 is that no carbon material is added.

[0152] Comparative Example 3

[0153] A high-strength fluidized solidified soil, comprising the following raw materials in parts by weight:

[0154] 572 parts of inorganic construction waste aggregate (obtained by crushing and screening discarded building concrete and discarded bricks and stones, with a particle size of 5-15 mm);

[0155] 229 pieces of engineering waste soil (obtained through drying and sieving of slag and silt, with a particle size of 0.15-5mm and a water absorption rate of 14.7%-20%);

[0156] Cement 79.5 parts (P.O42.5);

[0157] 56 parts of copper mine tailings;

[0158] 106 parts of composite curing agent;

[0159] 7.5 parts of carbon material;

[0160] 4.8 parts of polycarboxylate water reducer;

[0161] 91.8 parts of distilled water.

[0162] A method for preparing high-strength fluidized solidified soil, the method comprising the following steps:

[0163] S1. Add inorganic construction waste aggregate and tailings slag into the mixer according to the proportion and stir for 8 minutes;

[0164] S2. Add engineering waste soil, cement and carbon materials into the mixer according to the proportion and stir for 8 minutes;

[0165] S3, dissolving the polycarboxylate water reducer in distilled water and homogenizing to obtain a water reducer solution, pouring half of the water reducer solution into a mixer and stirring for 5 minutes, adding the remaining water reducer solution and continuing to stir until the slurry is completely fluidized in the mixer;

[0166] S4, adding composite curing agent into the mixer according to the proportion, stirring for 5 minutes, and obtaining high-strength fluidized solidified soil slurry;

[0167] S5. The high-strength fluidized solidified soil slurry obtained in S4 is loaded into the backfill tank and vibrated, and then cured for 24 hours under constant temperature and humidity conditions.

[0168] The difference between this comparative example and Example 1 is that no sisal fiber and basalt fiber are added.

[0169] Comparative Example 4

[0170] A high-strength fluidized solidified soil, comprising the following raw materials in parts by weight:

[0171] 572 parts of inorganic construction waste aggregate (obtained by crushing and screening discarded building concrete and discarded bricks and stones, with a particle size of 5-15 mm);

[0172] 229 pieces of engineering waste soil (obtained through drying and sieving of slag and silt, with a particle size of 0.15-5mm and a water absorption rate of 14.7%-20%);

[0173] Cement 79.5 parts (P.O42.5);

[0174] 56 parts of copper mine tailings;

[0175] 106 parts of polyacrylamide;

[0176] 7.5 parts of carbon material;

[0177] 3 parts of basalt fiber (density 2.5-2.8g / cm3, tensile strength 3.5-4GPa);

[0178] 4.8 parts of polycarboxylate water reducer;

[0179] 91.8 parts of distilled water.

[0180] A method for preparing high-strength fluidized solidified soil, the method comprising the following steps:

[0181] S1. Add inorganic construction waste aggregate, tailings and basalt fiber into the mixer according to the proportion and stir for 8 minutes;

[0182] S2. Add engineering waste soil, cement and carbon materials into the mixer according to the proportion and stir for 8 minutes;

[0183] S3, dissolving the polycarboxylate water reducer in distilled water and homogenizing to obtain a water reducer solution, pouring half of the water reducer solution into a mixer and stirring for 5 minutes, adding the remaining water reducer solution and continuing to stir until the slurry is completely fluidized in the mixer;

[0184] S4. Add water glass into the mixer according to the proportion and stir for 5 minutes to obtain a high-strength fluidized solidified soil slurry;

[0185] S5. The high-strength fluidized solidified soil slurry obtained in S4 is loaded into the backfill tank and vibrated, and then cured for 24 hours under constant temperature and humidity conditions.

[0186] The difference between this comparative example and Example 1 is that no composite curing agent and sisal fiber are added, and polyacrylamide is used as the curing agent.

[0187] Comparative Example 5

[0188] A high-strength fluidized solidified soil, comprising the following raw materials in parts by weight:

[0189] 572 parts of inorganic construction waste aggregate (obtained by crushing and screening discarded building concrete and discarded bricks and stones, with a particle size of 5-15 mm);

[0190] 229 pieces of engineering waste soil (obtained through drying and sieving of slag and silt, with a particle size of 0.15-5mm and a water absorption rate of 14.7%-20%);

[0191] Cement 79.5 parts (P.O42.5);

[0192] 56 parts of copper mine tailings;

[0193] 106 parts of polyacrylamide;

[0194] 7.5 parts of carbon material;

[0195] 4.4 parts of sisal fiber (length 3-4 cm, elongation at break 4%-6%);

[0196] 3 parts of basalt fiber (density 2.5-2.8g / cm3, tensile strength 3.5-4GPa);

[0197] 4.8 parts of polycarboxylate water reducer;

[0198] 91.8 parts of distilled water.

[0199] A method for preparing high-strength fluidized solidified soil, the method comprising the following steps:

[0200] S1. Add inorganic construction waste aggregate, tailings, sisal fiber and basalt fiber into the mixer according to the proportion and stir for 8 minutes;

[0201] S2. Add engineering waste soil, cement and carbon materials into the mixer according to the proportion and stir for 8 minutes;

[0202] S3, dissolving the polycarboxylate water reducer in distilled water and homogenizing to obtain a water reducer solution, pouring half of the water reducer solution into a mixer and stirring for 5 minutes, adding the remaining water reducer solution and continuing to stir until the slurry is completely fluidized in the mixer;

[0203] S4, adding composite curing agent into the mixer according to the proportion, stirring for 5 minutes, and obtaining high-strength fluidized solidified soil slurry;

[0204] S5. The high-strength fluidized solidified soil slurry obtained in S4 is loaded into the backfill tank and vibrated, and then cured for 24 hours under constant temperature and humidity conditions.

[0205] The difference between this comparative example and Example 1 is that no composite curing agent is added, but polyacrylamide is used as the curing agent.

[0206] test:

[0207] 1. Freeze-thaw cycle stability

[0208] The specimens were cast into blocks of 100×100×400 mm and tested for frost resistance using a NELD-FC810 computer-controlled concrete rapid freeze-thaw cycle testing machine according to ASTM C666 / C666M-03 “Standard Test Method for Rapid Freeze-Thaw Resistance of Concrete”.

[0209] The mass and dynamic elastic modulus were tested after every 25 cycles, and the mass loss and relative dynamic elastic modulus were calculated. The freeze-thaw failure criterion was a 5% mass loss or a 40% decrease in the relative dynamic elastic modulus.

[0210] The test results are shown in Table 1.

[0211] The compressive strength loss is tested after every 25 freeze-thaw cycles. The compressive strength test is performed on cubic specimens according to GB / T 50081. If the compressive strength loss exceeds 25%, the specimen is considered to be frozen-thaw damaged.

[0212] The test results are shown in Table 2.

[0213] Table 1

[0214]

[0215] Table 2

[0216]

[0217] 2. Compressive Strength

[0218] The specimen was cast into a block of 150×150×150mm. According to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the side surfaces during molding were used as the upper and lower pressure-bearing surfaces. At the same time, the center of the specimen was geometrically aligned with the press. The press was started and the load was applied. The loading speed was 0.8MPa / s. When the loading speed of the press was manually controlled, when the specimen was close to failure and began to deform sharply, the throttle of the testing machine should be stopped until failure, and the failure load should be recorded.

[0219] Measure the compressive strength of the specimens on the 7th, 14th and 28th day. Statistical data, collate the data measured on the three specimens and use the arithmetic mean as the compressive strength value of the group of specimens.

[0220] The test results are shown in Table 3.

[0221] Table 3

[0222]

[0223] 3. Splitting tensile strength

[0224] The specimen was cast into a block of 150×150×150mm. According to GB / T 50081-2019 “Standard for Test Methods for Physical and Mechanical Properties of Concrete”, the specimen was placed at the center of the lower pressure plate of the testing machine. The splitting pressure surface and the splitting surface should be perpendicular to the top surface of the specimen when it was formed. A circular arc pad and a pad strip were placed between the upper and lower pressure plates and the specimen. The pad and the pad strip should be aligned with the center line of the upper and lower sides of the specimen and perpendicular to the top surface when it was formed. The press was started and the load was applied. The loading speed was 0.8MPa / s. When the loading speed of the press was manually controlled, when the specimen was close to failure and began to deform sharply, the throttle of the testing machine should be stopped until it was destroyed, and the failure load was recorded.

[0225] The splitting tensile strength of the specimens was measured on the 7th, 14th and 28th day. The data of the three specimens were statistically analyzed and the arithmetic mean was used as the splitting tensile strength value of the specimens.

[0226] The test results are shown in Table 4.

[0227] Table 4

[0228] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 7d(MPa) 7.56 7.62 7.48 5.91 5.17 4.78 4.96 6.05 14d(MPa) 8.12 8.08 8.17 6.71 5.98 5.59 5.52 6.78 28d(MPa) 8.54 8.51 8.56 6.97 6.14 5.81 5.80 7.06

[0229] 4. Autogenous shrinkage

[0230] According to ASTM C1698-2009 "Standard Test Method for Self-Stress of Cement Paste and Cement Mortar".

[0231] The test results are shown in Table 5.

[0232] Table 5

[0233]

[0234] 5. Discussion of Results and Conclusions

[0235] 1. As can be seen from Table 1, none of the specimens of Examples 1-3 failed due to freeze-thaw failure, indicating that the high-type fluidized solidified soil of the present invention has good freeze-thaw resistance; the specimens of Comparative Examples 1, 4 and 5 failed due to freeze-thaw failure, while Comparative Examples 2 and 3 did not fail, indicating that the addition of the composite curing agent plays a major role in improving the frost resistance of the specimens.

[0236] 2. As can be seen from Table 2, none of the test specimens of Examples 1-3 were damaged by freeze-thaw, indicating that the high-flow solidified soil of the present invention still has stable compressive strength in a freeze-thaw cycle environment; Comparative Examples 1, 3 and 4 were damaged by freeze-thaw, while Comparative Examples 2 and 5 were not damaged, indicating that the addition of composite curing agent, sisal fiber and basalt fiber can improve the compressive strength and structural stability of the test specimens in a freeze-thaw environment. It is worth mentioning that although Comparative Example 5 was not damaged after 200 freeze-thaw cycles, its compressive strength loss rate was close to the critical value of the damage standard of 25%, which shows that the addition of a composite curing agent with a phase change energy storage function plays a major role in improving the compressive strength of the test specimens in a freeze-thaw environment; compared with the failure of Comparative Example 4, it can be concluded that in addition to the important role of the composite curing agent with a phase change energy storage function, the synergistic effect of the addition of sisal fiber is also indispensable for soil strength modification in a freeze-thaw environment.

[0237] 3. As can be seen from Table 3, the compressive strength of the specimens of Examples 1-3 can reach more than 96 MPa after 28 days, which is significantly improved compared with the specimens of Comparative Examples 1-5, indicating that the composite curing agent, pretreated carbon material, sisal fiber and basalt fiber and the synergistic effect between their materials all play an important role in improving the compressive strength.

[0238] 4. As shown in Table 4, the crack resistance of Examples 1-3 can reach more than 8.5 MPa after 28 days, which is significantly improved compared with the test pieces of Comparative Examples 1-5, indicating that the composite curing agent, pretreated carbon material, sisal fiber and basalt fiber and the synergistic effect between their materials all play an important role in improving the splitting tensile strength. Among them, it can be concluded from Comparative Example 1 compared with Comparative Examples 2-5 that the pretreated biochar and the two fibers (especially the synergistic effect of sisal fiber and modified core-shell polyacrylamide) play a major role in improving the tensile performance, followed by the composite curing agent.

[0239] 5. It can be seen from Table 5 that the autogenous shrinkage rate of the specimens of Examples 1-3 and Comparative Examples 1, 3, 4 and 5 is significantly reduced compared with the autogenous shrinkage rate of the specimen of Comparative Example 2. The pretreated biochar can change the relative humidity and pore structure inside the soil, so that the inside of the concrete can achieve the effect of internal curing, reduce the risk of cracking caused by uneven deformation of the specimen due to autogenous shrinkage, and improve the crack resistance and compression resistance.

[0240] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0241] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0242] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A high-strength fluidized solidified soil, characterized in that: The composition comprises the following raw materials in parts by weight: 550-594 parts of inorganic construction waste aggregate; 204-254 pieces of engineering waste soil; Cement 75-84 parts; Tailings 54-58 parts; Composite curing agent 98-114 parts; 3.8-11.2 parts of carbon material; Sisal fiber 2.9-5.8 parts; Basalt fiber 2.9-3.1 parts; Polycarboxylate water reducer 4-5.6 parts; 85-98.5 parts of distilled water; The inorganic construction waste aggregate is obtained by pre-processing of waste construction concrete and waste bricks and stones through crushing and screening; The engineering waste soil is obtained by drying and screening the slag and sludge. The tailings are copper ore tailings; The composite curing agent is mainly composed of core-shell modified polyacrylamide, waste brick powder and water glass, and the specific preparation steps are as follows: The core-shell modified polyacrylamide was dispersed in deionized water at room temperature and homogenized for 15-20 minutes, a crosslinking agent was added, and the mixture was stirred for 5-8 minutes, sodium bicarbonate was added, and the mixture was stirred until it was completely dissolved, waste brick powder was added, and the mixture was stirred until the waste brick powder was evenly dispersed in the system, water glass was added, and the mixture was stirred until the waste brick powder particles had no longer precipitation, and the mixture was allowed to stand for 12 hours to obtain a composite curing agent; The core-shell modified polyacrylamide is prepared by encapsulating polyethylene glycol and graphene oxide in polyacrylamide through free radical polymerization, and the specific preparation steps are as follows: Graphene oxide was ultrasonically dispersed in deionized water, acrylamide was added, and the mixture was stirred at 800 r / min for 30 min at room temperature. Polyethylene glycol was added and stirred at 800 r / min at 60 °C until the polyethylene glycol was completely dissolved. N,N-methylenebisacrylamide and tetramethylethylenediamine were added and stirred at 600 r / min for 20 min. Ammonium persulfate was added and homogenized for 3 min. The mixture was allowed to stand at 60 °C for 3 h to obtain core-shell modified polyacrylamide.

2. The high-strength fluidized solidified soil according to claim 1, characterized in that: The inorganic construction waste aggregate has a particle size of 5-15 mm.

3. The high-strength fluidized solidified soil according to claim 1, characterized in that: The particle size of the engineering waste soil is 0.15-5 mm, and the water absorption rate is 14.7%-20%.

4. The high-strength fluidized solidified soil according to claim 1, characterized in that: The mass ratio of the core-shell modified polyacrylamide, deionized water, crosslinking agent, sodium bicarbonate, waste brick powder and water glass is 0.2:(25-43):(0.4-2.0):2:(10-13):

17.

5. The high-strength fluidized solidified soil according to claim 1, characterized in that: The cross-linking agent is one of aluminum citrate, aluminum chloride and aluminum sulfate; the particle size of the waste brick powder is 0.05-0.15 mm; and the modulus of water glass is 2.2-2.

6.

6. The high-strength fluidized solidified soil according to claim 1, characterized in that: The usage ratio of the graphene oxide, deionized water, acrylamide, polyethylene glycol, N,N-methylenebisacrylamide, tetramethylethylenediamine and ammonium persulfate is 0.2g:12mL:2g:(12.09-13)g:0.02g:20μL:0.02g; the molecular weight of polyethylene glycol is 3000-10000.

7. The high-strength fluidized solidified soil according to claim 1, characterized in that: The carbon material is pretreated biochar, and the pretreatment method is as follows: Soak the biochar in water at 25°C for 24 hours, take it out and place it on a strainer until there is no continuous dripping, spread it flat and place it in a drying oven at 120°C to dry for 10-15 minutes.

8. The high-strength fluidized solidified soil according to claim 1, characterized in that: The sisal fiber is 3-4 cm in length and 4%-6% in elongation at break.

9. The high-strength fluidized solidified soil according to claim 1, characterized in that: The basalt fiber has a density of 2.5-2.8 g / cm3 and a tensile strength of 3.5-4 GPa.

10. A method for preparing high-strength fluidized solidified soil according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: S1. Add inorganic construction waste aggregate, tailings, sisal fiber and basalt fiber into the mixer according to the proportion and stir for 5-8 minutes; S2. Add engineering waste soil, cement and carbon materials into the mixer according to the proportion and stir for 5-8 minutes; S3, dissolving the polycarboxylate water reducer in distilled water and homogenizing to obtain a water reducer solution, pouring half of the water reducer solution into a mixer and stirring for 3-5 minutes, adding the remaining water reducer solution and continuing to stir until the slurry is completely fluidized in the mixer; S4. Add the composite curing agent into the mixer according to the proportion, stir for 3-5 minutes, and obtain a high-strength fluidized solidified soil slurry; S5. The high-strength fluidized solidified soil slurry obtained in S4 is loaded into the backfill tank and vibrated, and then cured for 24-48 hours under constant temperature and humidity conditions.

Citation Information

Cited By

  • Ocean anti-scour flow-state solidified soil material and preparation method and application thereof

    CN120328949A

  • Premixed flow state solidified soil roadbed backfill material and preparation method thereof

    CN121697102A